Quantifying inter- and intra-ply shear in the deformation of uncured composite laminates - S. Erland (Taylor & Francis Group, 2021)
Understanding the bending mechanics of uncured carbon fiber prepreg is vital for modeling forming processes and the formation of out-of-plane wrinkling defects. This article presents a modification of standard dynamic mechanical analysis (DMA) to characterize the viscoelastic bending mechanics of uncured carbon fiber prepreg using Timoshenko beam theory, along with an updated model describing inter-ply shear in uncured laminates. By post-processing DMA results, the analysis provides temperature and rate-dependent values of inter and intra-ply shear stiffness for a carbon fiber laminate and each individual ply with experimental results for AS4/8552 presented. The new methodology provides a means to parametrize process models, and also gives an indication of optimal manufacturing conditions to enable defect-free forming and consolidation processes.